Podstawowe założenia koncepcji systemu informacji marketingowych w przedsiębiorstwie eksportującym - Malinowski, Andrzej (Wydział Prawa i Administracji UAM, 1978)
Fundamental assumptions of a concept of marketing information system in an exporting enterprise are discussed in the article. The role of marketing information as a basis for management decision taking in exporting enterprises increases particularly under conditions of active foreign trade, in which fulfilment of economic tasks calls for efficiency of actions as on capitalistic markets so on socialist ones. The information needs connected with this situation create absolute necessity of determination of ways of planned formulating and steering transmission of marketing data in exporting enterprises. These requirements can be met by properly organized system of marketing information. The article deals with the essence and main features of marketing information system, its connections with market research carried up to the present in practice as well as with general principles of organization. It is a starting point for further works of the author in this field.
The Fundamental Assumptions of a Concept of Marketing Information System in an Exporting Enterprise